687.141.017.872.004.12 EVALUATION OF DEFORMATION PROPERTIES OF HIGHLY ELASTIC KNITTED FABRICS IN SPORTSWEAR DESIGN: Compression sportswear, knitwear - Monnopov, Joxongir; Kayumov, Jurabek; MAKSUDOV, Nabijon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article analyzes the modern range of compression materials, highlighting key factors such as the elasticity, deformation, and abrasion resistance properties of the materials. In the process of designing compression sportswear, selecting fabric samples and conducting tests to determine their mechanical properties is of significant scientific and practical importance. As a result of experimental studies, the elongation of materials was studied, and special testing equipment of the YG026A-III and YG026T models was used to assess the deformation properties. The deformation properties were evaluated, and elongation diagrams were provided, which will help improve the methods used to determine the operational characteristics of materials.